2019
DOI: 10.1186/s13023-019-1026-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient access to orphan drugs in France

Abstract: Background Since incentives were introduced to promote orphan drugs in Europe, several dozens of drugs have been registered at the European level. However, patient access on a national level remains very heterogeneous across Europe. This can be explained by healthcare organization and drug reimbursement, which are within the purview of each Member State. We studied access to orphan drugs in France from the patients’ point of view, including marketing but also ease of supply from patients’ perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…This gap, which was about 1.4 percentage points in the study by Espin et al (2.9% list growth vs. 1.5% net growth) [18] is not captured in this analysis. It is true, however, that list prices are also used for non-OMP expenditure, but it seems that the level of (confidential) discounting and rebates is higher for medicines used in hospitals rather than dispensed in pharmacies, and OMPs are usually used in hospital settings [18, 20]. Therefore, observed total expenditure will be overestimated within this study, especially for more recent years.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This gap, which was about 1.4 percentage points in the study by Espin et al (2.9% list growth vs. 1.5% net growth) [18] is not captured in this analysis. It is true, however, that list prices are also used for non-OMP expenditure, but it seems that the level of (confidential) discounting and rebates is higher for medicines used in hospitals rather than dispensed in pharmacies, and OMPs are usually used in hospital settings [18, 20]. Therefore, observed total expenditure will be overestimated within this study, especially for more recent years.…”
Section: Discussionmentioning
confidence: 87%
“…Fourth, the analyses are based on expenditure at list prices, which overestimates the value of the market. However, to our knowledge there is no information available comparing the level of discounting between OMPs and non-OMPs, although confidential discounts have been shown to be greater for medicines used in a hospital setting [18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, several country-specific population surveys assessing the societal preference for rarity were published. In contrast to the previously mentioned reports, they mostly concluded that there was no societal preference for rarity alone [ 24 , 26 , 27 , 35 , 38 , 39 , 42 46 , 63 , 73 , 75 , 78 – 80 , 87 , 92 , 93 , 99 , 111 , 112 , 114 , 116 , 132 , 151 , 157 , 161 , 167 , 173 , 182 , 198 , 205 , 208 , 212 , 213 , 217 , 252 254 ], but did find general preferences for considering equity in healthcare resource allocation, including preferential reimbursement for severe diseases without available alternatives [ 24 , 44 , 63 , 80 , 116 , 167 , 182 , 205 , 212 , 213 , 254 ]. Similarly, it was shown that healthcare professionals were not generally prioritizing rarity [ 43 , 182 ].…”
Section: Resultsmentioning
confidence: 74%
“…Access granted through exemption at the individual level (permission for one patient) National reimbursement at the discretion of health insurance company [ 19 ] The unmet medical need for an individual patient and availability of the product in another country, possibly for another indication [ 19 ] Tailored access for the patient with unmet medical needs to treatments for very rare conditions Permission is only granted on a case-to-case basis for one patient (labor-intensive/not suitable for large groups), differences in national regulations, not necessarily reimbursed (in the Netherlands). A supplying party is responsible for safety and follow-up [ 19 ] Temporary authorization of use (French ATU) Yescarta [ 30 ] National medicines agency [ 31 ] nATU: Requested by a physician (permission for one patient); cATU: Requested by drug manufacturer (permission for a (sub-)group of patients) [ 22 ] National French Ministry of Health and French National Health Insurance [ 20 ] Urgent unmet medical need, presumed efficacy, and safety based on scientific data [ 31 ] Access before market approval for patients with unmet medical needs, complete reimbursement, strong financial incentives for commercial companies [ 20 ] Under construction, different maturity levels in different legislations, and potentially large budget impact for health care systems IRB Milasen, Fanconi [ 23 , 24 ] Local (national) research board Researchers, often in collaboration with clinical experts Local Research funding Local (national) criteria for safe and responsible research Fast Only small-scale application, not sustainable and equitable Compounding CDCA (not SGT) [ 32 ] Hospital pharmacy; eventually National Health Care Institute [ 33 ] Treating physician Local Reimbursement at the discretion of health insurance companies; eventually uptake in national health care package may occur Production for individuals or very small groups of patients Medicines can be produced at a lower price than a commercial product Tension in regulatory framework (lack of precedents) Hospital exemption …”
Section: Market Approval As Atmps Through the Emamentioning
confidence: 99%
“…In France, the ATU system encompasses aspects of both compassionate use and named-patient use, but with a different system of reimbursement prior to market approval [ 20 ]. During the ATU validity period, products are entirely reimbursed by the French National Health Insurance, potentially having a large budget impact on the French healthcare system [ 21 ].…”
Section: Temporary Authorization For Use (Atu)mentioning
confidence: 99%